The approach of educational philosophy in overcoming social problem - Hassan, Aminuddin; Mohamad, Lukman @ Zawawi; Ismail, Habsah; Yusoff, Salwana (EuroJournals Publishing, Inc., 2009)
The purpose of this paper is to explore the philosophy of education approaches in solving social problems. These approaches are also considering the perspectives of some popular denomination and branches of philosophy of education that constantly discussing about social problem. This paper stressed that social problem is not just by seeing only from the mechanism; it’s also upon the basis on how it occurred or to avoid with wise evaluation on it.